Comparative assessment of FRP´S and steel bars applied on the reinforcement of concrete structures - Patinha, S. (2013)
Nowadays the sustainability of construction and the need for more sustainable construction solutions is one big concern in the construction field. This way, many times the FRP reinforcing materials are seen and sold as more sustainable and ecological options, when compared with steel or other metal based materials. This fact is essentially due to their non carbon dioxide corrosion characteristics that ensure longer service life and light-weight combined with high strength (Waldron, 2004). But the application of FRP bars for concrete reinforcement is a very specific application that deals with very different requirements and conditions. Due to that, the sustainability has to be assessed through the whole range of structural applications by specific tools, able to evaluate the real sustainability such as the Life Cycle Assessment (LCA) tools (Franzoni, 2011). To address this issue, a comparative study has been performed , among different concrete reinforcing materials such as steel, Glass fiber-reinforced Polymer (GFRP), Aramid fiberreinforced polymer (AFRP) and Carbon Fiber-reinforced Polymer(CFRP) and for two different structural applications: beam and slab. Therefore, the objective of this work is to compare the LCA of concrete structural elements, under the same ultimate and service load conditions, reinforced by steel and different FRPs.